Flavanone and Isoflavone Glucosylation by Non-Leloir Glycosyltransferases - Sepulveda-Boza, S (Elsevier B.V., 2016)
Flavonoids possess a wide range of biological activities. Their glycosylation is of considerable interest, as it often positively influences their pharmacokinetic and other molecular properties. We recently showed that two non-Leloir glycosyltransferases that use sucrose as carbohydrate donor, an amylosucrase from Neisseria polysaccharea (Ams-Np) and a glucansucrase from Streptococcus oralis (GtfR-So), were hardly able to glucosylate flavones, but accepted flavanes as substrates. We now examined compounds from two other flavonoid classes, flavanones and isoflavones for glucose transfer by these enzymes. Taxifolin was investigated as a flavanone analogue of both, the accepted pentahydroxyflavane catechin and the non-accepted pentahydroxyflavone quercetin. It was glucosylated by both enzymes, but much better by GtfR-So than by Ams-Np due to apparent strong inhibition of the latter. The acceptance of a collection of isoflavones strongly depended on the substitution pattern of the core. Only two of the 10 compounds examined yielded glucosides in satisfactory amounts. With these substrates, both enzymes catalyzed formation of a range of products, differing in the number of saccharide units. The structures of mono- and diglycosylated compounds obtained in higher amounts were elucidated. While GtfR-So attached glucose to taxifolin in the B ring at O4′, both enzymes glucosylated the isoflavones in the A ring at O7. All products were α-glucosides. Interglycosidic linkages formed by Ams-Np were α1-4. To our knowledge, this is the first report of glucosylation of flavanone and isoflavone aglycones by an amylosucrase. All characterized compounds have not previously been described. © 2016 Elsevier B.V.